2017
DOI: 10.3168/jds.2016-12367
|View full text |Cite
|
Sign up to set email alerts
|

Linseed oil and DGAT1 K232A polymorphism: Effects on methane emission, energy and nitrogen metabolism, lactation performance, ruminal fermentation, and rumen microbial composition of Holstein-Friesian cows

Abstract: Complex interactions between rumen microbiota, cow genetics, and diet composition may exist. Therefore, the effect of linseed oil, DGAT1 K232A polymorphism (DGAT1), and the interaction between linseed oil and DGAT1 on CH and H emission, energy and N metabolism, lactation performance, ruminal fermentation, and rumen bacterial and archaeal composition was investigated. Twenty-four lactating Holstein-Friesian cows (i.e., 12 with DGAT1 KK genotype and 12 with DGAT1 AA genotype) were fed 2 diets in a crossover desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 67 publications
3
33
0
Order By: Relevance
“…result of fumarate and monensin inclusion. These results are consistent with previous studies related to the supplementation of linseed oil in dairy cows and steers diets [67][68][69]. In the rumen, there are two pathways for propionate production; succinate pathway (the main pathway) and acrylate pathway [70].…”
Section: Plos Onesupporting
confidence: 92%
“…result of fumarate and monensin inclusion. These results are consistent with previous studies related to the supplementation of linseed oil in dairy cows and steers diets [67][68][69]. In the rumen, there are two pathways for propionate production; succinate pathway (the main pathway) and acrylate pathway [70].…”
Section: Plos Onesupporting
confidence: 92%
“…opposite was observed for the archaea to bacteria ratio. The few studies that have found a relationship are based on single time-point measurements, which used either post-mortem rumen digesta samples [38] or a relatively large number of animals [39]. The biological significance of the positive correlation of archaeal concentrations with CH 4 yield on d10 of this study are, however, not clear as the CH 4 emission data from the study of Van Gastelen et al [10] was measured only from days 13 to day 17.…”
Section: Plos Onementioning
confidence: 71%
“…These are often regarded as the synthetic proxy for microbial species and are typically clustered at 97% sequence similarity. However, the prokaryotic species definition remains a hotly debated topic without any satisfying solution so far [10][11][12] . Moreover, the 97% sequence similarity threshold is based on the complete 16S rRNA gene (~1500 nt), and although sequence variability is not evenly distributed it is routinely applied to short reads of 100-500 nt.…”
Section: Introductionmentioning
confidence: 99%